Iron (II) Polypyridyl Complexes as Antiglioblastoma Agents to Overcome the Blood-Brain Barrier and Inhibit Cell Proliferation by Regulating p53 and 4E-BP1 Pathways - Zhu, Huili; Dai, Chengli; He, Lizhen; Xu, Anding; Chen, Tianfeng (Frontiers in Pharmacology, 2019)
Background and purpose: It is urgently required to develop promising candidates to permeate across blood-brain barrier (BBB) efficiently with simultaneous disrupting vasculogenic mimicry capability of gliomas. Previously, a series of Iron (II) complexes were synthesized through a facile method, of which the anti-cancer activity was determined to a certain degree. Hence, the aim of this study was to evaluate anti-cancer activity of Fe(PIP)3SO4 against glioma cancer cells. Methods: Cytotoxic effects were determined via MTT assay, and IC50 values were utilized to evaluate the cytotoxicity. Cellular uptake of Fe(PIP)3SO4 between U87 and HEB cells was conducted by subtracting content of the complex remaining in the cell culture supernatants. PI-flow cytometric analysis was used to analyze cell cycle proportion. The reactive oxygen species (ROS) level induced by Fe(PIP)3SO4 were measured by DCF probe, ABTS assay was utilized to examine radical scavenge capacity of Fe(PIP)3SO4. To study the bind efficiency to Thioredoxin reductase (TrxR), Fe(PIP)3SO4 was introduced into solution containing TrxR 1. To verify if Fe(PIP)3SO4 could penetrate BBB, HBMEC/U87 coculture as BBB model was established and penetrating capability of Fe(PIP)3SO4 was tested. In vitro U87 tumor spheroids were formed to test the permeating ability of Fe(PIP)3SO4. Acute toxicity and biodistribution of Fe(PIP)3SO4 was tested on mice for 72 h. Protein profiles associated with U87 cells treated with Fe(PIP)3SO4 were determined by western blotting analysis. Results: Results showed that Fe(PIP)3SO4 could suppress cell proliferation by inducing G2/M phase cycle retardation and apoptotic pathways, which was related with expression of p53 and initiation factor 4E binding protein 1 (4E-BP1). In addition, Fe complex could suppress cell proliferation by downregulating ROS levels via scavenging free radicals and interaction with TrxR. Furthermore, Fe(PIP)3SO4 could permeate across BBB and simultaneously inhibited the VM-channel of U87 cells, suggesting favorable anti-glioblastoma efficacy. Acute toxicity manifested lower degree of the complex compared with cisplatin and temozolomide (TMZ). Conclusion: Fe(PIP)3SO4 exhibited favorable anticancer activity against glioma cells associated with p53 and 4E-BP1, accompanied with negligible toxic effects on normal tissues. Herein, Fe(PIP)3SO4 could be developed as a promising metal-based chemotherapeutic agent to overcome BBB and antagonize glioblastomas.